Microencapsulation of Annona crassiflora extract using maltodextrin: Material design and evaluation of antioxidant, antiglycation, and antiaging properties in vitro and in silico - Spera, Kamille Daleck [UNESP]; Gorni, Pedro Henrique; Bronzel-Junior, João Luiz [UNESP]; Granero, Filipe Oliveira [UNESP]; Figueiredo, Célia Cristina Malaguti; Santos, Hugo Henrique [UNESP]; Silva, Luciana Pereira [UNESP]; Perego, Patrizia; Debiagi, Paulo Eduardo Amaral; Nicolau-Junior, Nilson; da Silva, Regildo Márcio Gonçalves [UNESP] (Elsevier, 2025)
Annona crassiflora, a native Brazilian Cerrado fruit tree, is rich in bioactive compounds, particularly phenolic compounds and flavonoids, known for their antioxidant capabilities. The research addresses the limitations of seasonal fruit production by exploring the bioactive potential of leaves, aiming for sustainable harvesting practices. In view of this, the study aimed to investigate the antioxidant, antiglycation, and antiaging properties of A. crassiflora leaf extract (AcHE), exploring its potential for microencapsulation using maltodextrin. The methodology included the preparation of a hydroethanolic extract (AcHE) from A. crassiflora leaves, phytochemical analysis to determine total polyphenol, flavonoid, and tannin content using spectrophotometric techniques and GC–MS analysis. Antioxidant activity was assessed through DPPH radical scavenging, ferric ion reducing power (FRAP), inhibition of lipid peroxidation (TBARS assay), nitric oxide radical scavenging activity, and oxidative hemolysis tests. Antiglycation activity was evaluated by quantifying free amino groups using the OPA method in a glycation reaction mixture of bovine serum albumin (BSA) and ribose. The study showed the efficacy of AcHE in preventing oxidative stress, glycation, and premature aging, which are linked to chronic diseases. It also demonstrated the optimization of the microencapsulation process with maltodextrin, showing enhanced stability, bioavailability, and efficacy of the bioactive compounds present in A. crassiflora leaves for potential applications in the food, pharmaceutical, and cosmetic industries.